The dragonfly effect / 3 - Korman, Gordon (Korman, Gordon. Hypnotists, 2016)
"Is it a gift or is it a curse? Jax Opus can use his color-changing eyes to make people do what he wants. But soon Jax is pulled into a dangerous conspiracy devised by a mysterious group...and now they're going to make Jax do what they want"--Provided by publisher.